Perfluoroalkane substances in national samples from global monitoring plan projects (2017–2019). (November 2022) - Fiedler, Heidelore; Sadia, Mohammad; Baabish, Abeer; Sobhanei, Siamak
Abstract: The global monitoring plan (GMP) established under the Stockholm Convention on Persistent Organic Pollutants (POPs) had defined ambient air, human milk or blood, and water as core matrices to be analyzed and assessed for spatial and temporal distribution. Within projects coordinated by the United Nations Environment Programme (UNEP), developing countries were offered to have other matrices analyzed for perfluoroalkane substances (PFAS) in one experienced laboratory. A total of 266 samples from 26 countries located in Africa, Asia, and Latin America were collected during 2018–2019 and analyzed for 15 PFAS. The limits of quantification were 6.2 pg/g fresh weight for most PFAS. The statistical assessment of 262 samples, four were excluded due to extreme values, showed that across abiotic and biota samples, perfluorooctane sulfonic acid (PFOS) had the highest detection frequency (80%) and the highest median value (19.2 pg/g), followed by perfluorooctanoic acid (PFOA) with 73% and a median value of 7.67 pg/g. Among the matrices, water (55%), sediment (49%) and fish (44%) had the most complex pattern, i.e., number of PFAS quantified. Dairy products and chicken meat had less PFAS present. From the 137 foods, fish, meat, eggs, analyzed in this study, only two fish samples would exceed one of the limit values proposed by the European Commission. To assess human exposure, we suggest including dairy products and drinking water since selective and sensitive methods would allow quantification of the four proposed PFAS. Graphical abstract: Image 1 Highlights: Perfluorooctane sulfonic acid and perfluorooctanoic acid dominated in 262 samples. Perfluorobutanoic acid was negatively correlated to other perfluoroalkane acids. No regional differences were found in either abiotic or biota samples (3 PFAS). Analytical method sensitive and selective to quantify PFAS at LOQ of 6.2 pg/g fresh weight.